2022
DOI: 10.3390/ijerph19116675
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Forest Users’ Stress on Perceived Restorativeness, Forest Recreation Motivation, and Mental Well-Being during COVID-19 Pandemic

Abstract: Even though the COVID-19 pandemic has discouraged travel and people’s movements, the number of visitors to forests near cities which are easily accessible by private vehicle is increasing in Korea. This study aims to investigate the relationship between stress, perceived restorativeness, forest recreation motivation, and the mental well-being of forest users. A survey of forest users was conducted at three recreational forests near Seoul in the summer of 2020. A total of 1196 forest users (613 males and 583 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…In addition, the authors demonstrated that the remaining two strategies were predictors of increased forest use during the pandemic. Lee et al [27] confirmed in their study that a greater frequency of visiting forest areas leads to greater stress resistance. The authors argued that this was due to the phytoncide released by the trees.…”
Section: Contact With Nature and Mitigating The Negative Effects Of C...mentioning
confidence: 76%
See 2 more Smart Citations
“…In addition, the authors demonstrated that the remaining two strategies were predictors of increased forest use during the pandemic. Lee et al [27] confirmed in their study that a greater frequency of visiting forest areas leads to greater stress resistance. The authors argued that this was due to the phytoncide released by the trees.…”
Section: Contact With Nature and Mitigating The Negative Effects Of C...mentioning
confidence: 76%
“…These data should cover aspects such as ecosystem services (potential and supply), the condition of green spaces, and benefits to society, including health benefits, among others [45,70,104,105]. The availability of reliable data is especially important in the post-pandemic period, as the habits and needs of different user groups may have changed [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Yamazaki et al [106] emphasized that it is essential for spatial planners to consider short-and long-term changes in user needs.…”
Section: Cities' Spatial Policy-post-covid-19 Challenges and Lessons ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, it remains the responsibility of governments to recognize and acknowledge the demands for and benefits of forest recreation for the whole society and provide sufficient incentives for forest owners and managers to safeguard and produce an expanded, inclusive FES portfolio based on forests that are less vulnerable to disturbances. In Europe, this vision appears to overlap with the desired turn of the forestry sector toward closer-to-nature forestry management as a concept proposed in the EU Forest Strategy for 2030 (Larsen et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Limited research has focused on the effect of the COVID-19 epidemic on the increased movement of people in the forest environment and the exploitation of the positive effects of the forest on human health (e.g., [6,22,[34][35][36][37][38][39][40][41]). Moreover, there has been little research (e.g., [42]) on the effect of restrictions associated with the reduction in movement of people during the epidemic, including in the forest environment.…”
Section: Introductionmentioning
confidence: 99%